On planning the adoption of new video standards in social media networks: a general framework and its application to HEVC - Koziri, Maria; Papadopoulos, Panos K.; Tziritas, Nikos; Dadaliaris, Antonios N.; Loukopoulos, Thanasis; Stamoulis, Georgios I. (Social network analysis and mining, 2017)
In recent years, we have witnessed an explosion in the growth of social media networks, powered by the proliferation of handheld smart devices with high processing capabilities and a plethora of sensors including high-resolution cameras. A key component of information exchange in such networks, accounting for the majority of network traffic, is video. Currently, the de facto video coding standard in use is H.264/AVC which was sufficient in addressing the challenges posed by HD more than a decade ago, but is less than efficient in the new era of 4K smart device cameras and 8K TV screens. Given that newer standards exist and are capable of achieving higher compression rates at the same quality compared to H.264/AVC, we envision that within the next few years, the related industry will shift toward one of the newer video coding standards. For a social media network, such a transition poses manifold challenges, one of them being the need to transcode previous content in the newly adopted standard. In this paper, we illustrate a framework for performing such transition in a smooth manner. The framework, algorithms and strategies developed are applicable, perhaps with minor changes, regardless of the targeted standard for adoption. We detail on framework components through simulation experiments, using as a yardstick the adoption of high efficiency video coding. Results demonstrate that depending on the targeted social platform, different strategies should be applied, while the cost and benefits of the paradigm shift may vary significantly.